Tinjauan Literatur: Efektivitas Butionin Sulfoksimin Dalam Meningkatkan Sensitivitas Sel Kanker Terhadap Agen Kemoterapi Secara In Vivo - Khoerunnisa Azamy; Wahyu Utami (Pharmacon: Jurnal Farmasi Indonesia, 2022)
Glutathione (GSH) is one of the targets to overcome chemotherapy resistance. Cancer cells adapt by increasing the production of GSH which acts as an antioxidant to reduce the reactive oxygen species (ROS)-inducing of chemotherapy agents. GSH can bind to chemotherapy agents that are electrophile resulting a conjugate of electrophile-GSH which is more polar so it is easily excreted out of the body. Butionine sulfoximine (BS) is a GSH inhibitor that decrease the concentration of GSH in cells. BS is a γ-glutamyl- cysteine ligase (GCL) enzyme inhibitor that catalyzes the first steps of GSH synthesis. This literature review aims to evaluate the use of BS to sensitize cancer cells against chemotherapy in vivo. The literature search was carried out of two databases (Pubmed and Sciendirect) resulting in 357 journals. Furthermore, a selection process was carried out which yielded in 10 journals. BS synergize with chemotherapy of alkylating groups, vincristine, geftinib, and cytarabine+doxorubicin and significantly increases the effectiveness of therapy compared to chemotherapy only. However, BS delay cancer in initiation phase, and not in tumor progression phase. In vivo, the combination of BS and chemotherapy of alkylating groups, vincristine, geftinib, and cytarabine+doxorubicin reduce the tumor volume, cancer cell proliferation and also increasing the survival of experimental animals.